Pengembangan Supervisi Refleksi â€œGibbsâ€ untuk Peningkatan Kepatuhan Kebersihan Tangan Petugas Kesehatan - Muhammad Fandizal; Hanny Handiyani (Persatuan Perawat Nasional Indonesia Jawa Tengah, 2020)
Supervision is an actuating part of the management function to achieve the goals of the organization. Supervision of hand hygiene compliance 94 health workers conducted by infection, prevention, & control link nurse (IPCLN) using direct supervision methods. The purpose of developing indirect supervision is because direct supervision is not effective to be carried out, so the development of supervision reflection